Chemical composition of marine manganese nodules from the Pacific Ocean - K N Han; M P Hoover; D W Fuerstenau (PANGAEA, 2023)
Manganese nodules were selected from various potential mining sites of the Pacific ocean. They were dried by heating at 1000°C until total evaporation and ground to powder before their chemical analysis by atomic absorption spectrophotometry.